Pengaruh Pendidikan Rekreasi dalam Meningkatkan Kesehatan Mental dan Hubungan Social Siswa Sekolah Dasar - Alfiah Rizqi Azizah; Alif Saevul Ajib (Journal on Education, 2025)
Recreational education plays an important role in character building and mental health of elementary school students. This study discusses the implementation of effective recreational education to improve students' mental health and social relationships. By applying the principles of recreational education, systematic implementation steps and appropriate strategies, recreational education can improve students' self-awareness, self-confidence, and social skills. This study also identifies the challenges of implementing recreational education and presents practical solutions. This study uses qualitative research methods to analyze the implementation of recreational education in improving the mental health and social relationships of elementary school students. The main data sources come from scientific articles, academic books related to recreational education. The results of the study show that recreational education has an important role in improving the mental health and social relationships of elementary school students. With effective implementation, recreational education can help students develop balanced social, emotional, and cognitive abilities. Thus, recreational education can make a significant contribution to the formation of a healthy and quality generation.